Intervensi Augmented Reality: Meningkatkan Pendidikan Agama di Sanggar Belajar Kampung Baru - Mustofa, Rochman Hadi; Narimo, Sabar; Hermawan, Hardika Dwi; Kusuma, Muhammad Isnani (IKIP PGRI Bojonegoro, 2024)
ABSTRACTThe inadequacy of institutions offering religious education to students at Sanggar Belajar Kampung Baru, Kuala Lumpur, Malaysia, is an urgent issue. Challenges related to immigration documentation and the absence of a structured curriculum in Community Learning Centers (CLC) contribute to the low level of religious knowledge among students. Although primary school years are crucial for acquiring basic knowledge of Islam and daily worship practices, CLC students face significant difficulties. In response, the Community Engagement for International Partnership (PkM-KI) team introduced Augmented Reality Cards (ARCard) as a new educational tool aimed at helping students learn prayer recitation. The main features of ARCard involve video presentations and three-dimensional objects, enhancing the learning experience. ARCard is specifically designed to offer guidance on prayer recitation and can be accessed via smartphone. The results show student enthusiasm, indicating that learning prayer recitation has become more accessible even without direct parental guidance. These findings underscore ARCard's potential as a significant tool for enhancing student participation in religious education at CLC Kampung Baru. The next recommended step is a comprehensive long-term evaluation of ARCard's impact on improving religious knowledge and learning motivation among students, providing valuable insights for the development of holistic learning programs in the future.Keywords: Augmented Reality, Sanggar Belajar, Community Learning Center, Learning MediaABSTRAKKetidakcukupan lembaga yang menawarkan pendidikan agama kepada siswa di Sanggar Belajar Kampung Baru, Kuala Lumpur, Malaysia, adalah masalah mendesak. Tantangan terkait dokumentasi imigrasi dan tidak adanya kurikulum terstruktur di Community Learning Center (CLC), yang mengatur pengajaran mata pelajaran Islam, berkontribusi pada rendahnya tingkat pengetahuan agama di kalangan siswa. Meskipun tahun-tahun sekolah dasar adalah periode tepat untuk memperoleh pengetahuan dasar tentang Islam dan praktik ibadah sehari-hari, siswa di CLC menghadapi kesulitan mencolok. Sebagai tanggapan, tim Community Engagement for International Partnership (PkM-KI) memperkenalkan Kartu Augmented Reality (ARCard) sebagai alat pendidikan baru yang bertujuan membantu siswa dalam belajar pembacaan doa. Fitur utama ARCard melibatkan presentasi video dan objek tiga dimensi, meningkatkan pengalaman belajar. ARCard ini dirancang khusus untuk menawarkan panduan tentang pembacaan doa dan dapat diakses melalui smartphone. Hasil kegiatan menunjukkan antusiasme siswa, bahwa belajar pengajian doa menjadi lebih mudah diakses bahkan tanpa bimbingan orang tua. Temuan ini menggarisbawahi potensi ARCard sebagai alat signifikan untuk meningkatkan partisipasi siswa dalam pendidikan agama di CLC Kampung Baru. Langkah selanjutnya yang disarankan adalah evaluasi jangka panjang yang komprehensif mengenai dampak penggunaan ARCard terhadap peningkatan pengetahuan agama dan motivasi belajar di kalangan siswa, memberikan wawasan berharga untuk pengembangan program pembelajaran holistik di masa depan.Kata kunci: Augmented Reality, Sanggar Belajar, Community Learning Center, Media Pembelajaran